2020
DOI: 10.3390/nu12082468
|View full text |Cite
|
Sign up to set email alerts
|

A Traditional Korean Diet with a Low Dietary Inflammatory Index Increases Anti-Inflammatory IL-10 and Decreases Pro-Inflammatory NF-κB in a Small Dietary Intervention Study

Abstract: Chronic low-grade inflammation may increase the risk of chronic disease, while diets rich in anti-inflammatory components may reduce it. To determine the anti-inflammatory properties of the traditional Korean diet (K-diet) that comprises high amounts of vegetables, fiber and phytochemicals, moderate amounts of legumes, and low amounts of animal fat, ten obese women aged 50–60 years were randomly assigned to the K-diet or control diet group. The control diet was a Westernized Korean diet commonly consumed in Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
4
9
0
1
Order By: Relevance
“…The persons having the KBD were lower in the blood concentrations of hemoglobin A1c, triglyceride, CRP, and WBC than those having other diets in the present study. Consistent with our study, those with a KBD have shown high anti-inflammatory properties and the lowest incidence of metabolic syndrome in previous studies [ 49 , 50 , 51 ]. These results suggest that the adults with KBD had a lower inflammatory response than those with RBD or WBD [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The persons having the KBD were lower in the blood concentrations of hemoglobin A1c, triglyceride, CRP, and WBC than those having other diets in the present study. Consistent with our study, those with a KBD have shown high anti-inflammatory properties and the lowest incidence of metabolic syndrome in previous studies [ 49 , 50 , 51 ]. These results suggest that the adults with KBD had a lower inflammatory response than those with RBD or WBD [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our study, those with a KBD have shown high anti-inflammatory properties and the lowest incidence of metabolic syndrome in previous studies [ 49 , 50 , 51 ]. These results suggest that the adults with KBD had a lower inflammatory response than those with RBD or WBD [ 49 ]. Therefore, ET-R was interpreted as KBD, which has a typical anti-inflammatory function.…”
Section: Discussionsupporting
confidence: 93%
“…A diet enriched with nutrients that are known to have anti-inflammatory properties such as vitamins C, D, and E, beta-carotene, polyunsaturated fatty acids, flavonoids, and dietary fiber can be a low inflammatory diet [ 119 ]. Interestingly, the host blood vitamin levels are associated with IBS symptoms.…”
Section: Dietary Modulation For the Relif Of Ibs Symptomsmentioning
confidence: 99%
“…The dietary inflammatory index can measure an individual's dietary inflammation potential (15). A higher DII score can predict Increased levels of inflammation markers (including interleukin 6 and c-reactive protein) (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%